Analysis of Concepts and Propositions through Multi-Representation Based Inquiry Learning on Colligative Properties - Herunata, Herunata; Fauziah, Putri Nanda; Pramudita, Fisky Ayudya Citra; Natasya, Shella (Universitas Negeri Surabaya, 2024)
Chemistry is a science that studies the composition, structure, and properties or changes of matter. In chemistry, there are three levels of representation namely macroscopic, submicroscopic, and symbolic. Chemistry is a branch of science that requires students to have an understanding of concepts and mathematical skills, one of which is colligative properties. The aim of this research is to analyze the concept of colligative properties so that students don’t have misconceptions and can enhance their understanding through a multi-representation approach. The method used is the scientific approach, based on a series of five main learning experiences: Observing, Questioning, Reasoning, Associating and Communicating. Information collection techniques include concept maps, concept analysis, and propositions. Colligative properties consist of vapor pressure lowering, boiling point elevation, freezing point depression, and osmotic pressure. The van't Hoff factor is present in most colligative properties where the solute is an electrolyte substance.